1995
DOI: 10.1038/hdy.1995.102
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy and clonal diversity in an arctic cladoceran

Abstract: Genome size determinations were coupled with allozyme and mtDNA studies to gain insights into the origin of polyploidy and clonal diversity in populations of Daphnia tenebrosa from Churchill, Manitoba. Allozymic variation at five enzyme loci allowed the detection of 32 clones. Analyses of 73 populations in 1981, 27 in 1987 and 45 in 1991 revealed that clonal frequencies were relatively stable and that D. tenebrosa was more clonally diverse (average of three clones per pond) than other species of the D. pulex c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 30 publications
1
45
0
Order By: Relevance
“… Daphnia tenebrosa is genetically highly variable relative to the other species (Table 3), which suggests a comparably high long-term effective population size. Some variation might have originated from introgressive hybridization (before the transition to asexuality or via rare sexual reproduction), but we propose that a large number of clones (often polyploid [62]) occurring across vast expanses of the Holarctic slow down the lineage sorting and yields paraphyletic genealogies with respect to D . pulicaria (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“… Daphnia tenebrosa is genetically highly variable relative to the other species (Table 3), which suggests a comparably high long-term effective population size. Some variation might have originated from introgressive hybridization (before the transition to asexuality or via rare sexual reproduction), but we propose that a large number of clones (often polyploid [62]) occurring across vast expanses of the Holarctic slow down the lineage sorting and yields paraphyletic genealogies with respect to D . pulicaria (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the difference between the 2 freshwater copepod groups and the marine group is probably not related to their different habitat, but is a result of the individual characteristics of the different species. In contrast to copepods, cladocerans had a lower and more constant DNA content, which is probably due to their 'miniature' genome size (Beaton & Hebert 1989, Dufresne & Hebert 1995.…”
Section: Biochemical Differences Between Freshwater and Marine Speciesmentioning
confidence: 94%
“…salt spray, fluctuating conductivity/ salinity levels) than bluff B. Previous work by Dufresne & Hebert (1995) examined changes in clonal composition and clonal diversity in Daphnia tenebrosa populations (another member of the D. pulex species complex) in tundra ponds at Churchill. They found relatively stable clonal distributions and clonal compositions in these habitats over a 10-year (1981 -1991) period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous genetic work, particularly focusing on the Churchill Daphnia pulex complex (Weider 1987;Weider & Hebert 1987a,b;Wilson & Hebert 1993;Dufresne & Hebert 1995;Weider et al 1999a,b), has shown that this Arctic complex includes of a mixture of distinct lineages/ species that are obligately parthenogenetic and that include both diploid (non-melanic) and polyploid (melanic) clones. Work on melanic clones in this complex (Weider 1987;Weider & Hebert 1987a,b) revealed microgeographic heterogeneity in their distributions that was strongly influenced by physico-chemical variation among rock pools, in particular salinity gradients.…”
Section: Introductionmentioning
confidence: 99%